Response in root development of Arabidopsis thaliana to leaf extract of Moringa oleifera - Ortiz-Rojas, Luz Yineth; Suárez-Botello, Jean Carlos; Chaves-Bedoya, Giovanni (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
The root growth response is mediated by hormones that participate in all stages of plant growth and development. A good root system guarantees anchoring and absorption of nutrients for the metabolic processes required in the developmental stages. Cytokinins (CK) and auxins (AIA) are hormones that play an important role in the development of the root system. Moringa oleifera has cytokinins, so the application of their extracts can have an effect on the development of the root system. In order to understand the root response to the Moringa oleiferaextract, we used an in vitro system with Arabidopsis thaliana and two experiment conditions. (A) Seeds germinated directly in MS medium with application of the Moringa oleifera extract at different dilutions, which determined how the primary root (PR) growth was affected. (B) Plants were germinated and grown for 8 days in the MS medium, without lateral roots (LR), and transferred to media with different dilutions of the extract. The results showed that (A) the best dilution of Moringa oleifera base extract (KOH 0.05 M) for the germination stimulation was seen in the dilutions of 1 mL, 1.5 mL and 2.0 mL, as well as the treatment with trans Zeathine riboside (ZR) with a concentration of 60 μM, and (B) the basic extract of Moringa oleifera in a ratio of 1.5: 0.5 (extract: KOH 0.05 M) was the best treatment for the development of the primary root (PR) and lateral roots (LR). Further studies are needed to determine the validity of these results in field.